Clinico-Pathological Correlation in the Classification of Leprosy - Poudel, Anuj; Shah, Anita; Khatiwada, Sulochana; Samdurkar, Ashok (Journal of Universal College of Medical Sciences, 2019)
INTRODUCTION:- Leprosy is one of the major health problems in Nepal, caused by Mycobacterium leprae. Histopathological examination is considered as important tool for proper classification of the disease. This study was carried out to study the histopathological features of leprosy in skin biopsies and classify based on microscopy, bacterial index to correlate with clinical presentations.MATERIAL AND METHODS:- A retrospective observational study was done at Department of Pathology of Universal College of Medical Sciences (UCMS) Bhairahawa for 2 years from 1st November 2015 to 31stOctober 2017 and total 68 cases were analysed. Cases in which histopathological diagnosis of leprosy was made or considered differential diagnosis were selected for study. Ridley and Jopling classification was used histologically to make diagnosis of leprosy. Copies of issued histopathology reports, that are preserved in the department routinely were used to obtain data pertaining to age, sex, clinical information and histopathological findings.RESULTS:- This study included 68 patients diagnosed histologically as leprosy. Histopathological examination of the skin biopsies of 68 patients revealed that, the maximum histopathological cases 28 (41.17%) are BT followed by 15 cases (22.05%) of IL (15) and 9 (13.23%) of TT. Complete parity between clinical diagnosis and histopathology was observed in 55.88 % and disparity was seen in 44.12%.CONCLUSION:- For proper classification of Leprosy, correlation of clinical and histopathological features along with bacterial index is more useful than considering any of the single parameter.